1975
DOI: 10.1017/s0007114575000414
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary calcium and phosphorus on the retention and excretion of lead in rats

Abstract: 1. Rats were given diets containing different amounts of calcium, phosphorus and lead.2. Pb retention was greatly increased when the diets contained less Ca or P than the minimum estimated requirement of the rat.3. The release of Pb already incorporated into the skeleton was inhibited by diets low in Ca but was not affected by diets low in P.4. The retention of Pb given intraperitoneally was not affected by dietary Ca or P.5. It can be concluded that dietary Ca and P influence the absorption of Pb by the gut a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 22 publications
(4 reference statements)
4
24
0
Order By: Relevance
“…Rather, calcium-deprived rats had decreased excretion and thus increased body retention of lead. This observation agrees with the work of Quarterman and Morrison (29), who noted that the release of lead already incorporated into the skeleton as a result of previous lead dosing was inhibited by the subsequent feeding of diets low in calcium. The physiological mechanism whereby low calcium diets increase lead retention is not known, but Goyer speculated that the site of action may be the kidney (25).…”
Section: Minerals Calciumsupporting
confidence: 92%
See 1 more Smart Citation
“…Rather, calcium-deprived rats had decreased excretion and thus increased body retention of lead. This observation agrees with the work of Quarterman and Morrison (29), who noted that the release of lead already incorporated into the skeleton as a result of previous lead dosing was inhibited by the subsequent feeding of diets low in calcium. The physiological mechanism whereby low calcium diets increase lead retention is not known, but Goyer speculated that the site of action may be the kidney (25).…”
Section: Minerals Calciumsupporting
confidence: 92%
“…Barltrop and Khoo showed that halving the recommended level of phosphate increased lead uptake by rats in shortterm experiments but to a slightly lesser degree than halving the calcium (27). On the other hand, Quarterman and Morrison found that feeding 33 and 70% of the recommended levels of calcium and phosphate, respectively, caused similar increases in lead retention in long-term studies (29). Both groups agreed that feeding diets low in both calcium and phosphate resulted in roughly additive effects on lead uptake or retention.…”
Section: Minerals Calciummentioning
confidence: 99%
“…[20], phosphorus [8,15], and sulfur [21,22]. The disappearance curves for lead excretion in blood, plasma, hematic cells, and some other soft tissues can be expressed as sums of exponential functions.…”
Section: Zincmentioning
confidence: 99%
“…Infants have a relatively high retention as compared to adults [7]. Indications have been found that lead interferes with the metabolism of calcium [8][9][10][11][12][13][14][15][16], magnesium [17], strontium [9], copper [1,18], iron [18,19]…”
mentioning
confidence: 99%
“…An alteration in bone or teeth of binding, more permanent deposition and the redistribution of lead would be expected in association with a variety of normal and clinical conditions, for example: (a) during early development, (b) continued growth at the epiphyses until maturity, (c) conditions that involve bone remodeling or resorption and (d) during pregnancy (69,(91)(92)(93). At these times, the lead may be more mobile than in quiescent periods.…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%